INTEGRATION OF ARTIFICIAL INTELLIGENCE TOOLS IN TEACHING ENGLISH AT SECONDARY SCHOOLS IN UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The rapid evolution of Artificial Intelligence (AI) has fundamentally reshaped multiple sectors, including education, where it is increasingly viewed as a catalyst for systemic transformation. In the domain of English language teaching (ELT), AI technologies offer sophisticated mechanisms for adaptive instruction, automated evaluation, speech processing, predictive analytics, and content generation. For Uzbekistan, a country actively modernizing its educational infrastructure and prioritizing foreign language proficiency, the integration of AI tools into secondary school English instruction represents both an opportunity and a strategic necessity.